Low Birth-Body Weight as Wasting Predictor over Children Aged 6-59 Months in Indonesia - Sri Nuryani Wahyuningrum; Ika Puspita Asturiningtyas; Slamet Riyanto (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2022)
Approximately ten percent of children under five in Indonesia have suffered from wasting. Children with low birth body weight are considerably more at risk of suffering such disease. This current study aimed to analyze the relationship between low birth body weight and other risk factors of wasting among Indonesian children. This study utilized data from the 2018 Indonesian National Basic Health Research (Riskesdas). In total, 60,451 children aged 6-59 months were included. The data were analyzed using bivariate and logistic regressions. According to the data analysis, children with low birth-body weight had significantly higher odds of being wasted compared to children with normal birth-body weight (OR=1.5, 95%CI=1.3-1.8). In addition, boys and younger children (6-23 months) were 1.3 times more susceptible to wasting (OR=1.3, 95%CI=1.2-1.4). Unemployed fathers and mothers comprised of 1.3 and 1.1 times, respectively, to increase the risk of child wasting (OR=1.3, 95%CI=1-1.7; OR=1.1, 95%CI=1-1.2). Mothers with a low education level contributed to an increase in wasting prevalence 1.1 times (OR=1.1, 95%CI=1-1.2). Children who were lack of vitamin A supplements had a 1.2 times more chance of being wasted (OR=1.2, 95%CI=1.1-1.3). This research eventually suggested that low birth-body weight was the dominant factor in child wasting in Indonesia. Programs for improving the nutritional status of pregnant women and children with low birth-body weight should therefore be implemented intensively and comprehensively.